Reducing the risk to marine ports from invasive mosquito species, zika, dengue, chikungunya viruses and filariasis - Kollars, Thomas; G. Kollars, Peggy; Hulsey, Bannie (International Journal of Medicine, 2016)
Background: Mosquitoes are the principal vector of pathogens to humans throughout the world. Ports are a primary means to which invasive mosquito species and the pathogens they carry are introduced into new areas and where the mosquito species was once eradicated.Methods: The ports of Porto Cortes (Honduras) and Savannah Port, (USA) were evaluated using the Bioagent Transport and Environmental Modeling System (BioTEMS) invasive species model to determine what species would be most likely to invade and survive in the Jebel Ali Port area (UAE). The Porto Cortes study site was evaluated to determine if mosquito control using ecofriendly pesticides was practical at the port of origin. Conclusion: The Bioagent Transport and Environmental Modeling System TIGER model provides information that can be utilized to interdict and control invasive mosquito species to reduce the risk they become permanently established. The receiving ports were at risk from mosquito invasion, however, because of niche parameters, the Savannah Port was at risk from four invasive species from Honduras and the Jebel Ali Port was at risk from Ae. albopictus from Porto Cortes and Savannah and Ae. vexans from Savannah. Mosquito control was obtained at the point of origin and optimal surveillance and control sites were identified.